Substitution Of Potato Flour In Mangkok Cake Making - Putri, Syandra Meylani; Gusnita, Wiwik; Syarif, Wirnelis; Siregar, Juliana (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research aims to analyze the effect of potato starch substitution on the quality of cupcakes by adding 20%, 40% and 60% potato starch. This type of research is pure experimental research with a completely randomized design (CRD) method consisting of 4 treatments and 3 repetitions. The object of this research is cupcakes with potato starch substitution of 20%, 40%, 60% for the quality of the cupcakes. The data collection technique for this research was carried out using organoleptic tests given to 5 expert panelists, namely lecturers in Family Welfare Science, Padang State University. The independent variable in this research is potato flour. The dependent variable of this research is the quality of the cupcakes produced including shape, color, aroma, texture and taste. The data analysis technique used is Analysis of Variance (ANOVA) to analyze organoleptic test data. The data that has been obtained is then tabulated in table form and analyzed according to each data test. Then data analysis is carried out, if the data obtained by Fcount is greater than Ftable then proceed with the Duncan test. The results of this research show that there